Mengukur Persistensi Inflasi: Studi Komparasi Delapan Kabupaten/Kota di Jawa Timur - Setyo Tri Wahyudi; M. Khusaini; Rihana Sofie Nabella (Pusat Penelitian, Badan Keahlian DPR RI, 2021)
Inflation is becoming one of the critical variables in the economy. Any movement in inflation will cause some changes to fundamental economic variables, such as economic growth and unemployment. Therefore, inflation becomes a variable that is often observed and tested, both theoretically and empirically. Stable inflation is a prerequisite for sustainable economic growth, which ultimately benefits the improvement of people’s well-being. Using city-level inflation data in East Java, this study aims to measure inflation’s persistence at the city level in East Java. The persistence of inflation indicates the speed at which the inflation rate returns to its equilibrium level after a shock. This study will also analyze the causes of persistence in eight cities in East Java. In this study, to measure the degree of inflationary persistence, the study used an Autoregressive Univariate Model. The test results found that (1) inflation in eight cities in East Java tended to fluctuate throughout the research period. The highest inflation occurred in Probolinggo City, while the lowest was in Madiun City. The most significant contributors to inflation are food groups. Then (2) the result obtained is the degree of inflation persistence in eight cities in East Java is still relatively high, so it requires attention from regulators. Moreover, the persistence of inflation is caused by high inflation expectations or leading to forward-looking. Based on the findings, the government needs to devise a measured strategy to control inflation to be stable, such as optimizing the Regional Inflation Control Team (TPID).Keywords: inflation, persistence, autoregressiveAbstrakInflasi menjadi salah satu variabel penting dalam ekonomi. Setiap pergerakan inflasi akan menyebabkan beberapa perubahan terhadap variabel fundamental ekonomi, seperti pertumbuhan ekonomi dan pengangguran. Oleh karena itu, inflasi menjadi variabel yang seringkali diamati dan diuji, baik secara teoritis maupun empiris. Pertumbuhan ekonomi dapat berjalan dengan baik apabila didukung oleh angka inflasi yang stabil dan kemudian akan berguna untuk meningkatkan kesejahteraan penduduk. Menggunakan data inflasi tingkat kabupaten/kota di Jawa Timur, penelitian ini bertujuan untuk mengukur persistensi inflasi di tingkat kabupaten/kota di Jawa Timur. Persistensi inflasi menunjukkan kecepatan tingkat inflasi untuk kembali ke tingkat ekuilibriumnya setelah adanya suatu shock. Selain itu, penelitian ini juga akan menganalisis penyebab persistensi di delapan kabupaten/kota di Jawa Timur. Untuk mengukur derajat persistensi inflasi, penelitian ini menggunakan Model Univariate Autoregressive (AR). Berdasarkan hasil pengujian, diperoleh temuan bahwa (1) inflasi di delapan kabupaten/kota di Jawa Timur cenderung berfluktuasi sepanjang periode penelitian. Inflasi tertinggi berada di Kota Probolinggo, sedangkan yang terendah adalah Kota Madiun. Komoditas penyumbang inflasi terbesar dari kelompok bahan makanan, contohnya telur ayam ras, beras, ayam ras, tomat sayur, bawang merah, dan daging sapi. Kemudian (2) hasil yang diperoleh adalah derajat persistensi inflasi di delapan kabupaten/kota di Jawa Timur masih terbilang tinggi sehingga memerlukan perhatian dari regulator. Selain itu, persistensi inflasi ini disebabkan oleh tingginya ekspektasi inflasi atau mengarah ke forward looking. Berdasarkan temuan, pemerintah perlu menyusun strategi yang terukur dalam mengendalikan inflasi supaya stabil, seperti mengoptimalkan peran Tim Pengendali Inflasi Daerah (TPID).Kata kunci: inflasi, persistensi, autoregressive